Accumulation of polystyrene microplastics induces liver fibrosis by activating cGAS/STING pathway. (1st May 2022) - Shen, Rong; Yang, Keren; Cheng, Xin; Guo, Changlei; Xing, Xiqing; Sun, Haonan; Liu, Disheng; Liu, Xiangwen; Wang, Degui
Abstract: The environmental pollution from microplastics has caused concern from the whole society due to its harm to organisms. However, the effect of microplastics on liver damage and fibrosis remains unclear in the case of long-term accumulation. The present study demonstrated that the 0.1 μm microplastic could enter hepatocytes from circulation and result liver damage even at a low concentration. Microplastic exposure could induce DNA damage in both nucleus and mitochondria, by which the dsDNA fragment was translocated into cytoplasm and triggered the DNA sensing adaptor STING. The activation of cGAS/STING pathway initiated the downstream cascade reaction, the NFκB translocated into nucleus and upregulated pro-inflammatory cytokines expression, and thus facilitating liver fibrosis eventually. Furthermore, inhibition of STING could alleviate the liver fibrosis via blocking the NFκB translocation and fibronectin expression. This study provided a valuable insight to elucidate the potential risk and mechanism of hepatic toxicity and fibrosis induced by microplastics. Graphical abstract: Image 1 Highlights: Micro-PS induced DNA damage and release in nucleus and mitochondria. cGAS/STING pathway activation was involved in inflammation and liver fibrosis. STING inhibitor alleviated liver fibrosis via blocking proinflammatory signaling. 0.1 μm micro-PS performed well permeability in cells and accumulated in liver. 1 μm micro-PS could hardly enter the cells.